Lighting design basics - Karlen, Mark.; Benya, James; Spangler, Christina (Hoboken : Wiley, 2012)
"The essential book of lighting for professional designers, now updated and revisedProviding the fundamental information new designers need to succeed in a concise, highly visual format, the Second Edition of Lighting Design Basics presents realistic goals that can be used as a guide to create simple yet impressive lighting designs and when collaborating with professional designers on more complex projects.Drawing on real-world case studies-- from kitchens to doctors' offices--the book is packed with attractive, helpful illustrations, making it an invaluable resource for students, as well as interior designers and architects studying for professional licensing exams. Authored by leading lighting designers with decades of experience Offers straightforward coverage of lighting concepts and techniques Contains design scenarios for more than twenty different types of spaces Lighting is a basic, yet difficult-to-master element of interior design. Lightning Design Basics changes that, putting the power to create in the hands of the designer"--
"The essential book of lighting for professional designers, now updated and revised. Providing the fundamental information new designers need to succeed in a concise, highly visual format, the Second Edition of Lighting Design Basics presents realistic goals that can be used as a guide to create simple yet impressive lighting designs and when collaborating with professional designers on more complex projects"--
.
Includes bibliographical references (page 233) and index.
Keywords: Lighting; Lighting, Architectural and decorative; ARCHITECTURE / Interior Design / Lighting